Measurement and Sorting of MSMEs Business Performance Rating Using Analytical Hierarchy Process - Isnaeni Yuli Arini; Tiara Verita Yastica (School of Industrial and System Engineering, Telkom University, 2022)
This research was conducted in an enterprise that provides venture capital assistance to its 876 Micro, Small, and Medium Enterprises (MSME) partners to measure and sort the performance of their business. The enterprise wished for a business performance calculation system that is more reliable and utilized more than one criterion. In addition, the enterprise also desired to give rewards to MSMEs with the most excel accomplishment, so they need to know which MSMEs are the most developed among others. This study uses focus group discussions and existing data to obtain the appropriate performance measurement criteria. The determination of the weight of the importance of each criterion was carried out using the Analytical Hierarchy Process (AHP) method using pairwise comparison techniques and its consistency is measured using the transitive property and consistency ratio. The proposed method is emphasized on ease of use and delivery to stakeholders but still capable of acquiring the performance calculation. The calculation includes the increase or decrease rate of the business performance for each MSME, and after sorting the rating, the most accomplished MSME also can be found. The application of this method also can help the stakeholder to reach consensus swiftly.